Beginning Oracle Database 11g Administration - Fernandez, Iggy (Apress, 2012)
In the ancient Chinese classic text Tao Te Ching, Lao Tzu (“Old Master”) says, “The tree which fills the arms grew from the tiniest sprout; the tower of nine stories rose from a (small) heap of earth; the journey of a thousand [miles] commenced with a single step.” I wrote Beginning Oracle Database 11g Administration to help you take the first steps of your Oracle Database journey. It’s the book I wish I’d had when I first started using Oracle Database so many years ago. It’s the book that I would have liked to have given to the many IT colleagues and friends who, over the years, have asked me to teach them the basics of Oracle Database. I started my own journey more than 10 years ago when my manager at the time, Bill Schwimmer, gave me the chance to become an Oracle Database administrator back in the days of Oracle 7. Books on Oracle Database were fewer then, and I relied on printed copies of the manuals, which I had to share with the rest of the team; this was in the days before Google, when Netscape Navigator had just appeared on the scene.